IMPLEMENTASI PERATURAN WALIKOTA SEMARANG NOMOR 83 TAHUN 2023 DALAM MENDUKUNG KEBIJAKAN PENDIDIKAN INKLUSIF DI KOTA SEMARANG - Fadia Ryona Fasya; Lusia Astrika (Journal of Politic and Government Studies, 2026)
This study aims to analyze the implementation of Semarang Mayor Regulation Number 83 of 2023 concerning the Establishment of Disability Service Units and Character Education for Students in supporting inclusive education policy in Semarang City. This research employs a qualitative approach with data collection techniques through triangulated interviews, observation, and documentation involving the Semarang City Education Office, Rumah Duta Revolusi Mental (RDRM), schools, parents of students with disabilities, as well as non-disabled students. The analysis applies the policy implementation theory of George C. Edward III, which includes the variables of communication, resources, disposition, and bureaucratic structure. In addition, the study also adopts the Index for Inclusion framework through three dimensions: creating inclusive cultures, producing inclusive policies, and evolving inclusive practices. The results indicate that the indicators of policy implementation have been achieved in the aspects of communication, implementers’ disposition, and bureaucratic structure, as reflected in clear coordination and service mechanisms among schools, the Education Office, and RDRM. Within the Index for Inclusion framework, the indicators of creating inclusive cultures, producing inclusive policies, and evolving inclusive practices have also been achieved through psychological assessments in the affirmative pathway of the New Student Admission System, psychoeducation for teachers, and adjustments to the learning process based on professional recommendations. However, the resource indicator has not been fully achieved due to limited human resources and the high service workload. Supporting factors include a clear regulatory foundation, the commitment of policy implementers, and coordination among stakeholders. Meanwhile, inhibiting factors involve limited human resources and restricted service capacity. This study concludes that policy implementation has been supported by structured coordination mechanisms but still requires strengthening in the resource aspect.